Domestic Resource Mobilization, Financial Access and Inclusion for Inclusive Growth in Nigerian - Obasi, Nwele J.; N. , Ngene Amuche; A., Uduimoh Anthony (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
This paper is a search light beamed to the investigation of the existing level of domestic resource mobilization, financial access and inclusion for inclusive growth in Nigeria, progressive policy development of government and implementation. Cohesive management of domestic resource mobilization, financial access and inclusion for inclusive growth are the driving force of all vibrant economy of the developed societies of the world, and a panacea to high level productivity of developing nations. Domestic resource mobilization, financial access and inclusion for inclusive growth are elements of political economy; it deals with both micro and macro-economics, with macroeconomics as the branch of economics concerned with the aggregate, or overall, economy. Macroeconomics deals with economics factors such as total national output and income, unemployment, balance of payments, and the rate of inflation, and is distinct from microeconomics, which is the study of the competition of the output such as the supply and demand for individual goals and services, the way they are traded in markets, and the pattern of their relative prices. At the basis of macroeconomics is an understanding of what constitutes national output, or national income, and the related concept of gross national product (GNP), with the GNP being the total value of goods and services provided in an economy during a given period of time, usually a year. This study is aimed at accessing the potentials available to Nigeria through efficient and effective mobilization of domestic resources, access to finance, and inclusion for inclusive growth. Objective of the study is to determine what needs to be done to thoroughly harness domestic resourcemobilization, financial access and inclusion for inclusive growth to galvanize the Nigerian economy. The research question is on the determination of whether domestic resource mobilization, financial access and inclusion help to galvanize inclusive growth. Methodology to be used is primary and secondary data concerning comparative development through domestic resource mobilization, financial access and inclusion for inclusive growth. Results of the finding in the research reveals that there are talents, skills,knowledge and creative skill-banks in Nigeria that are not harnessed because there is not enough support by governments to progressive policies to galvanize the advance lens of the talents, skills, knowledge and creative banks that exist in various corners where there are lots of human resource waste bins). Proffered as solution, is the need for Nigerian government to invest properly and effectively on development strata without discrimination or sentiments.